2014
DOI: 10.1063/1.4894424
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs/GaAsP strain balanced multi-quantum wires grown on misoriented GaAs substrates for high efficiency solar cells

Abstract: Quantum wires (QWRs) form naturally when growing strain balanced InGaAs/GaAsP multi-quantum wells (MQW) on GaAs [100] 6° misoriented substrates under the usual growth conditions. The presence of wires instead of wells could have several unexpected consequences for the performance of the MQW solar cells, both positive and negative, that need to be assessed to achieve high conversion efficiencies. In this letter, we study QWR properties from the point of view of their performance as solar cells by means of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…For the current device structures, the base region was measured to be p-type with the background concentration as high as − × − 1 2 10 cm 19 3 from the electrochemical capacitance voltage measurement. The second factor can be addressed by strain compensation, employing tensile-strained GaAs 1À y P y barriers [8], which allow for the increased thickness of the base region, as reported in the context of InGaAs/GaAsP MQW solar cells [19][20][21]. For the best extraction of the electron and hole pairs generated in the based region, the GaAsP thickness has to be thin enough with high P fraction so that there is weak electron-hole confinement in the QW, allowing the formation of minibands Intensity (a.u.…”
Section: Resultsmentioning
confidence: 99%
“…For the current device structures, the base region was measured to be p-type with the background concentration as high as − × − 1 2 10 cm 19 3 from the electrochemical capacitance voltage measurement. The second factor can be addressed by strain compensation, employing tensile-strained GaAs 1À y P y barriers [8], which allow for the increased thickness of the base region, as reported in the context of InGaAs/GaAsP MQW solar cells [19][20][21]. For the best extraction of the electron and hole pairs generated in the based region, the GaAsP thickness has to be thin enough with high P fraction so that there is weak electron-hole confinement in the QW, allowing the formation of minibands Intensity (a.u.…”
Section: Resultsmentioning
confidence: 99%
“…Методом металлоорганической газовой эпитаксии создавались GaAs p−i−n-структуры, в которые вводилось различное число (3,4,5,7,10) In 0.4 Ga 0.6 As квантово-размерных объектов (рядов). Анализировалось влияние числа рядов на зависимость V oc −C (напряжение холостого хода -кратность солнечного излучения), которая после калибровки превращается в V oc −J g -характеристику, эквивалентную искомой безрезистивной темновой ВАХ.…”
Section: заключениеunclassified
“…Эксперименты по внедрению квантовых объектов (точек, ям и других подобных объектов) в p−i−n-структуру проводятся в настоящее время из-за возможности улучшения характеристик полупроводниковых приборов (фотодетекторов, солнечных элементов, лазерных диодов и др. [1][2][3][4][5]).…”
Section: Introductionunclassified
“…Recently, it was found that photoluminescence (PL) lifetime for such an undulated InGaAs/GaAsP superlattice exceeds 1 ms owing to asymmetric carrier escape, or photo‐charging , which is not observable for a planar superlattice. Such long lifetime of the carriers trapped in the wires is expected to make carrier collection easier than the case of planer superlattice.…”
Section: Introductionmentioning
confidence: 99%